Dampak Manajemen Rantai Pasok Halal terhadap Kinerja Rantai Pasok: Tinjauan Literatur Sistematis - Yusuf, Riziq Maulana; Rusfian, Effy Zalfiana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study examines how halal supply chain management influences supply chain performance in food and logistics settings where product integrity, food safety, and sustainability are increasingly scrutinized. The review is motivated by fragmented empirical findings and limited synthesis on how digital technologies shape the performance effects of halal practices. A systematic literature review was conducted by searching the Scopus database for English journal articles in business, management, and accounting published between 2014 and 2025. From an initial pool of 9,780 records, stepwise screening with the keywords supply chain management, halal supply chain management, supply chain performance, and halal product yielded nine studies for synthesis and bibliometric mapping with VosViewer. The findings indicate that strict physical segregation, end to end traceability, robust certification and labelling, organisational capabilities, and knowledge management enhance efficiency, flexibility, halal compliance, and market trust, leading to stronger operational and sustainable performance. The review also highlights opportunities for technologies such as blockchain, the Internet of Things, artificial intelligence, and immersive virtual environments to improve transparency and reduce contamination and data fraud risks. These insights call for cross industry empirical testing of mediating mechanisms and infrastructure readiness to support more adaptive halal supply chains.